EFL TEACHERS’ LINGUISTIC SELF-CONCEPT IN A STUDY ABROAD (SA) PROGRAM - Mardiningrum, Arifah (Journal of Foreign Language Teaching and Learning, 2017)
The current study investigated the experiences and linguistic self-concept of six EFL teachers from Indonesia in a Study Abroad (SA) program. The participants were six EFL teachers who were in their first year of an SA program in the United States of America. All of them were enrolled asstudents in postgraduate programs in different universities in the U.S. when the data were collected. The data collection was conducted through semi-structured interviews through videocalls. The study found that the participants encountered linguistics experiences related to certainlinguistic features and culture. In addition to those experiences, certain forms of linguistic selfconcept were also found. Participants? linguistic self-concept showed that they perceived that they were not proficient enough in English, their English was very formal, they were proficient on certain area, and their struggle was not a unique experience. It can be concluded that as learners in an SA program, EFL teachers experienced what were normally experienced by learners in an SA program in general.